Elastic, electronic, optical and thermoelectric properties of the novel Zintl-phase Ba2ZnP2 - Khireddine, A.; Bouhemadou, A.; Maabed, S.; Bin-Omran, S.; Khenata, R.; Al-Douri, Y. (Solid state sciences, 2022)
We report and discuss the results of a detailed first-principles calculations of the structural, elastic, electronic, optical and thermoelectric properties of the new Zintl phase dibarium zinc diphosphide Ba2ZnP2. The calculated structural parameters using the GGA-PBEsol functional are in excellent agreement with the available experimental counterparts. From the monocrystalline elastic constants numerically estimated through the stress-strain technique, a set of related properties, viz., mechanical stability, elastic anisotropy, brittle/ductile character, anisotropic sound velocities, polycrystalline elastic moduli, including isotropic bulk modulus, shear modulus, Young's modulus, Poisson's ratio, average sound velocity and Debye temperature, are deduced. The electronic and optical properties are investigated through the state-of-the art FP-(L)APW + lo method with the accurate TB-mBJ potential. Ba2ZnP2 is an indirect semiconductor with a gap of 1.24 eV. The charge-carrier effective masses are calculated. The valence band maximum is less dispersive than the conduction band minimum. The microscopic origins of the electronic states composing the energy bands are determined via the PDOS diagrams. Topological analysis of the charge density shows that a covalent character is dominantly ruling the Zn–P bond inside the block ZnP4, while an ionic bonding is mainly ruling the bond between the cation Ba and the polyanion ZnP4. Frequency-dependent macroscopic linear optical functions are predicted in a wide energy range 0–30 eV. Within the visible spectra, the calculated magnitude of the absorption coefficient, reflectivity and refractive index are in the ranges ∼4−35×104cm−1, 29−36% and 3.18−3.47, respectively. The semi-classical Boltzmann transport theory within the constant relaxation time approximation is used to study the thermoelectric properties. The title compound has a figure of merit of ∼1.77 at 300 K, which makes it a potential candidate for thermoelectric applications. [Display omitted] •Some fundamental physical properties of the novel Zintl-phase Ba2ZnP2 are explored.•It is mechanically stable with moderate stiffness and a significant elastic anisotropy.•It is an indirect bandgap semiconductors with mixed covalent-ionic bond characters.•It exhibits an import absorption of the electromagnetic radiation in the visible and UV spectra.•It can be classified among the TE materials of performant thermoelectricity candidate for thermoelectric applications.